Análisis de rendimientos y productividad de mano de obra para la empresa La Puerta del Sol Equipo Constructor S.A. - Brenes-Serrano, Johan Octavio (Instituto Tecnológico de Costa Rica, 2014)
The next project is the result of an investigation into the performance of labor in the construction of prefabricated buildings and homes. Observations and measurements of which data to be analyzed statistically were taken were made. The practice was focused in the center of challenges COSEVI projects located in Heredia and room in a house located in Guápiles. Construction is a process that is divided into different stages, among them is the planning and costing of the project, which is why it is very important a good costing in steps, and this can only be done if known resources involved in the construction process. This project aims to address the lack of representative yields of similar projects, for proper planning and budgeting. The project developed, will result in a database yields labor and materials in order to support the company to calculate budgets yields obtained labor. And so incorporate them into the spreadsheet of company budgets. To achieve most of the activities involved in construction for prefabricated systems and resources used in each analyzed.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2014.
Keywords: Formulación de proyectos; Rendimiento laboral; Mano de obra; Productividad del trabajo; Costos de producción